MAPPING DAN SCHEDULLING INFORMASI SEKOLAH MENENGAH KEJURUAN DALAM MENINGKATKAN PELAYANAN SEKOLAH BERBASIS WEB - Dani Pradana Kartaputra; Siti Aliyah; Linda Apriyanti (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2016)
Mapping and scheduling the use of the waterfall method (clasicc life cycle) to perform knowledge discovery from web usage data. One function of the mapping and scheduling is to improve school-based services website is the mapping and scheduling of web users that can be used for data processing efficiently, and effectively. The main problems faced by the identification of a problem on the analysis of the school, where it is a major issue in the scheduling of school subjects .. The method developed is with waterfall paradigm (clasicc life cycle). Functions presentation of a concept map / mapping a way to show the concepts or stopik proposition in the field of study. Implementation of mapping and scheduling using PHP and Mysql. From the test results showed that the proposed mapping and scheduling have this level of effective and efficient in data processing. Keywords : mapping dan schedulling, school, student, service